Covid-19 Pandemic and Behavioural Response to Self-Medication Practice in Western Uganda - Dare, Samuel S.; Eze, Ejike Daniel; Isaac, Echoru; Usman, Ibe Michael; Ssempijja, Fred; Bukenya, Edmund Eriya; Ssebuufu, Robinson (medRxiv, 2021)
Self-medication has become is a serious public health problem globally posing great risks, especially with the increasing number of cases of COVID-19 disease in Uganda. This is may be partly because of the absence of a recognized treatment for the disease, however, the prevalence and nature differ from country to country which may influence human behavioural responses. Aim This study aimed to investigated the beharioural response of the community towards selfmedication practices during this COVID-19 pandemic and lockdown. Methods A cross sectional household and online survey was conducted during the months of June-to- August. The study was conducted among adult between age 18 above in communities of western Uganda who consented to participate in the study. Study participants were selected using a convenience sampling technique and sampling was done by sending a structured online questionnaire via Google forms and a printed copies questionnaire made available to other participants that did not use the online questionnaire Results The percentage of respondents that know about self-medication is (97%) and those that practice self-medication are approximately (88%). 97% of respondents have heard about self-medication either through health workers, media, family members, friends and/or school while 3% said they have not heard about self-medication. The percentage of respondents who practiced selfmedication during COVID-19 pandemic is 57% while those that did not is 43%. There is statistically difference in the number of those that practice self-medication and those that do not p < 0.005 at 95% confidence interval. Also there was a statistically significant decrease in the number of respondents that practice self-medication during COVID-19 pandemic lockdown compare to the practice before the pandemic lockdown p < 0.05 at 95% confidence interval. Conclusion Our investigation showed adequate knowledge of self-medication and high level of selfmedication practice with a decrease in self-medication practices during the COVID-19 pandemic lockdown compared to the practice before the lockdown.
Keywords: Covid-19; Self-medication; Pandemic; Behavioural response; Lockdown; Drugs